ELECTROMECHANICAL COMPLEX WITH COMPENSATED ASYNCHRONOUS MACHINES - Chuenko, R.; Makarevich, S.; Gavriluk, V. (Energy and Automation, 2016)
The construction of autonomous electromechanics complex with compensated asynchronous machines is offered.